"We expect seniors to be able to prepare and recover from a cyclone as well as younger members of this community": Emergency Management's Expectations of Older Adults Residing in Aging, Remote Hamlets on Australia's Cyclone-Prone Coastline. (24th July 2017) - Astill, Sandra; Miller, Evonne
Abstract: Objective: To investigate the extent to which older residents feel they can remain "self-reliant" during future natural disasters and to compare the findings with the viewpoints of local policy-makers and with those charged with caring for the elderly both on a day-to-day basis and in times of crisis. Methods: This study used an array of non-probability snowballing techniques to seek the participation of senior citizens over the age of 65 years, emergency services officers, community health carers, and local government disaster managers located in aging, remote, coastal Australian communities vulnerable to cyclones and storm surges. All respondents participated in either a face-to-face personal interview or a focus group, with senior citizens also completing a self-administered questionnaire. Results: This research found a discrepancy between policy expectations and the experiences of both the elderly and those who care for them, as well as a lack of understanding with regard to the term "self-reliant." Conclusions: These results highlight the inability of older adults in aging, remote, coastal Australian communities to remain "self-reliant" in the future, impacting both disaster management policies and the future capacity of these communities to remain resilient. ( Disaster Med Public Health Preparedness . 2018;12:14–18)